Teaching Graphic Communication and Techniques to senior phase Technology learners: A guide for teachers - Mlondie Thlokomelo Sibiya; Thokozani Isaac Mtshali (International Journal of Education and Teaching Zone, 2025)
This study examined the teaching of Graphic Communication and Techniques to senior phase Technology learners. A quantitative research approach was adopted, and a case study design was employed. To a population of 7 teachers and 156 learners in Capricorn District, Limpopo in South Africa, a convenient sample of 13 teachers and 149 learners were used. This study collected data through questionnaires, observations and archive analysis. This study revealed that 76.92% of sampled teachers taught learners different structures using freehand technique and single point perspective, but this had a negative impact on leaners ability to use drawing tools as no teacher attempted to use and encourage learners to draw using adequate set squares. It was interesting to see that only 38.46% of teachers emphasised the need to use different colours in drawings to improve learners spatial and cognitive skills. Some of the leaners activities showed that different colours were used even though the drawings were not correct and appealing. Only 69.23% of teachers taught learners the use of correct line types, sadly learners were not receptive of this emphasis as most of them had drawings which were drawn in bold lines and not neat. In light of the emergent findings, this study recommended that teachers should engage in lesson study approaches with other colleagues teaching Technology in order to strengthen their grasp of learner-centred approaches that are appropriate for teaching graphic communication and techniques.